The transition of Chilean adolescents from the child welfare system to the adolescent justice system: a continuation or an accumulation of adverse factors? - Zambrano, Viviana; Fernández-Pacheco, Gloria; Salazar-Muñoz, Miguel (Frontiers in Psychology, 2023)
Research on juvenile delinquency and adolescent maladjustment indicates that the beginning of these processes is found in the relationship between multiple risk factors at the individual, family and community levels in this population. The objective of this research was to analyze the risk factors related to the transition from the child welfare system to the adolescent justice system in a group of Chilean male adolescents (n = 108), aged 14–18 years, grouped according to their membership in the child welfare system, the adolescent justice system or both systems. Through a quantitative methodology, variables associated with risk factors were examined by means of the Risk and Resource Evaluation Form FER-R and the Risk and Criminogenic Needs Inventory IRNC instruments. Logistic regression analysis found that the adolescent population within the child welfare system was more likely to enter the adolescent justice system if the following risk factors were present: weak family supervision, consumption of drugs, socially maladaptive peer relationships, and risky free time. These results emphasize that child welfare system interventions should focus on parental support and the management of socio-community networks to prevent re-entry of the adolescent population into the justice system.